Can a Growth Mindset Be Successfully Cultivated in Adolescents? A Three-Year Longitudinal Study of an Intervention Program in a Rural School in China - Yu, Ruxian (Best Evidence in Chinese Education, 2025)
In response to the debates on the effectiveness of growth mindset interventions and their applicability in various cultural contexts, the study applied a localized intervention program in a rural school in China’ Yangtze River Delta region through a randomized controlled experiment and evaluates its effects longitudinally using the difference-in-differences method. Its research findings revealed that the localized growth mindset intervention program significantly strengthened the growth mindset of the subjects, that the intervention had long-term effects, that it had a greater positive effect on growth mindset development in younger students and those with lower initial levels of this mindset, and that the enhancement of the students’ growth mindset via the intervention program successfully improved their learning behavior.